Heterodox mediations. Notes on Walid Raad's The Atlas Group. Issue 1 (1st January 2019) - Baumann, Stefanie
ABSTRACT: The Atlas Group appeals to philosophical thinking in multiple ways—both through its aesthetic figuration and its conceptual references. Presented as a foundation dedicated to the research and the compilation of documents on Lebanese contemporary history and organized in the form of an invented archive, this artistic project deliberately coalesces real and fictitious elements and confronts, subversively, Western views on the socio-political reality of the Middle East with implicit knowledge and experiences from the region. The singular constitution of this curious archive subtly undermines the rational classification to which it alludes, thereby frustrating unilateral appropriations. Moreover, the question of the mediation of subjective experience and factual reality is consistently raised through the hysterical documents. This article aims to deploy how Walid Raadâ€™s project subtly criticises objectivist hegemonic claims by confronting divergent, often incommensurate approaches to the conflictual reality in Lebanon and its appropriation by media, historiography and politics.